Sentido modal de la evidencia en Husserl: modalidad versus modalización - Anton, Ivana (2013)
Phenomenological evidence has been characterized as fulfillment of a meaning intention, comprehension that tends to assimilate evidence to fulfilled consciousness, without making justice to the essential and mutual implication of emptiness and fullness that constitutes it out of its horizontic-intentional kind. The horizon, typically configured, offers the field of possible fulfillment; that is why it can be said that evidence takes place in a consciousness of possibility, namely, a modal one, though in an originary material and not doxic or positional sense,because it is the first one that is incumbent upon relationships of fulfillment. Modality that essentially characterizes evidence does not reveal itself then in the possible modalization as positional modification of a unitary content, but in its “outlined” material configuration of fullness and emptiness that gives somethingas something referring to other possibilities as moments of its own validity.